2023
DOI: 10.1111/joim.13624
|View full text |Cite
|
Sign up to set email alerts
|

Risk of fractures and postfracture mortality in 3980 people with primary biliary cholangitis: A population‐based cohort study

Abstract: Background Morbidity in primary biliary cholangitis (PBC) is multifactorial. Osteoporosis related to cholestasis is an extrahepatic complication of PBC. It is not fully established to what extent people with PBC have an increased risk for fractures, and if mortality after a fracture is increased, compared to the general population. Methods All Swedish people with PBC diagnosed between 2001 and 2016 were identified from the National Swedish Patient Register using ICD‐10 codes. Incident fractures were ascertaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…12 In patients with cirrhosis, alcohol consumption, tobacco use, and sedentary lifestyle are additional risk factors for the development of osteoporosis. 12 Patients with cirrhosis are at a higher risk for osteoporosisrelated fracture compared to the general population, which can dramatically impact quality of life and mortality [13][14][15][16][17][18][19][20] (Table 2). In addition, patients with cirrhosis are more likely to develop an infection, acute kidney injury, surgical complications and have a higher mortality after a fracture compared to patients without liver disease [16][17][18][19] (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…12 In patients with cirrhosis, alcohol consumption, tobacco use, and sedentary lifestyle are additional risk factors for the development of osteoporosis. 12 Patients with cirrhosis are at a higher risk for osteoporosisrelated fracture compared to the general population, which can dramatically impact quality of life and mortality [13][14][15][16][17][18][19][20] (Table 2). In addition, patients with cirrhosis are more likely to develop an infection, acute kidney injury, surgical complications and have a higher mortality after a fracture compared to patients without liver disease [16][17][18][19] (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…A review study reported that the prevalence of osteoporosis in PBC ranged from 20% to 44%, with an increase in prevalence correlating to disease progression and a high incidence of fractures (10-20%) (6). A comprehensive analysis of 3,980 PBC patients revealed a significantly higher fracture risk and post-fracture mortality in these patients compared to matched controls from the general population (7). However, the relationship between PBC and osteoporosis is subject to debate.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding: Risk of fractures and postfracture mortality in 3980 people with primary biliary cholangitis Dear Editor, We read with great interest the research conducted by Schönau et al, published in this issue of the Journal of Internal Medicine. The authors utilized a Swedish nationwide database and conducted a retrospective cohort study to evaluate the risk of fracture and related mortality events in patients with primary biliary cholangitis (PBC) [1]. Through providing large-scale real-world evaluation, results provided in the current study could be clinically important because proper evidence was lacking in previous studies.…”
mentioning
confidence: 99%